Amanah Ikhtiar Malaysia (AIM): a story of the programme success / Zuraidah Mohamed Isa ... [et al.] - Mohamed Isa, Zuraidah; Ali, Norhidayah; Ibrahim, Dahlia; Abd Rahman, Nurul Hayani (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Microcredit is a small business loan offered to people in need. The ideas of microcredit are not new. It was introduced in the 1970s by Prof. Muhammad Yunus who was actively involved in poverty alleviation programmes. In 1976, he visited very poor househol ds in the village of Jobra, Bangladesh, there, he learned that by providing capital and better opportunities, these poor households can improve their livelihood. He used his personal money to provide financial assistance to 42 poor individuals. Satisfied w ith the repayment of these loans, he was prompted to expand the financial assistance using a more structured banking system. After many efforts and reaching out numerous banks, Grameen Bank was finally established in 1983. Grameen Bank was formed to offer small loans to the poor through small weekly installments. The success story of Grameen Bank has become worldNobel Peace in 2006.